Ginsenoside Rg3 Ameliorates Stress of Broiler Chicks Induced by Escherichia coli Lipopolysaccharide - Bi, Shicheng; Qu, Yiwen; Shao, Jianjian; Zhang, Jianrong; Li, Weihao; Zhang, Li; Ni, Jingxuan; Cao, Liting (Frontiers in Veterinary Science, 2022)
Escherichia coli lipopolysaccharide is a prominent cause for inflammatory damage and loss of immune homeostasis in broiler chicks. Ginsenosides are found to have anti-inflammatory and antioxidant effects. However, whether ginsenosides protect broiler chicks against stress induced by Escherichia coli lipopolysaccharide challenge has not been demonstrated. This study aimed to investigate the protective effect of ginsenosides Rg1, Re and Rg3 on Escherichia coli lipopolysaccharide-induced stress. Our results showed that Rg3 ameliorated growth inhibition and fever, as well as decreased the production of stress-related hormones in broilers with stress. The protective effect of Rg3 on the stressed chicks may be largely mediated by regulating inflammatory response and oxidative damage. Moreover, RT-qPCR results demonstrated that Rg3 upregulated mRNA expression of mTOR, HO-1 and SOD-1. These results suggested that ginsenoside Rg3 and ginsenoside products contains Rg3 deserve further study for the control of immunological stress and inflammation in broiler chicks.